The Influence of Attitude, Subjective Norm, and Perceived Behavioral Control on Purchase Intention of Apple iPhone: A Study of Generation Z Consumers in Indonesia - Elvira Benita; Geraldy Pratama Teguh (iBuss Management, 2023)
As digital technology proliferated and more smartphone brands have emerged globally, researchers are eager to investigate how brands need to adapt to the current demand of consumers, particularly in high-population developing countries like Indonesia. Gen Z consumers have contributed a sizable portion to the Indonesian smartphone market, especially in luxury brands, one of which is the Apple iPhone. As there is still a limited amount of research conducted to explain the market's luxury consumption behavior, this research aims to investigate the key factors that influence Indonesian Gen Z consumers' purchase intention of Apple iPhone using the theory of planned behavior. The research will dive deeper into the significance and relationship between attitude, subjective norm, and perceived behavioral control toward consumers’ purchase intention. A quantitative approach with the simple random sampling method will be conducted to analyze the results using the PLS-SEM, with T-statistics test to examine the research hypotheses. The results of the study indicated that subjective norm is the most important determinant of purchase intentions for Apple iPhone products. Subjective norm is also found to moderate the relationship between attitude and perceived behavioral control towards luxury purchase intentions. The results of the study will greatly assist business institutions and marketing professionals to formulate better marketing strategies in Indonesia that align with the behavior of this demographic segment. Keywords: attitude, subjective norm, perceived behavioral control, purchase intention, Generation Z, luxury brand, theory of planned behavior.